Unpacking the Scarborough Charter: A Dialogue with Karima Hashmani - Eva Cupchik (Atlantis)
Eva Cupchik self-identifies as a queer, cisgendered, Jewish (Ashkenazi) woman and independent scholar. She is currently a federal policy analyst, specializing in equity, diversity, and inclusion. She defended a doctorate at Western University’s Theory Center (conferred 2020) that explored, through in-depth interviews, how Indigenous students experience identity, ways of knowing, health, truth, and reconciliation. She recently completed a Master of Arts within Carleton University’s Law and Legal Studies department, focusing on equity, accessibility, diversity, and inclusion (EDI), as it implicates health policy, such as Medical Assistance in Dying legislation. Her post-PhD research engages with queer, Jewish, and Indigenous (First Nations, Inuit, Métis) knowledge systems, transnational feminist, and Eurocentric phenomenology using quantitative and qualitative research methods. She continues to support 2SLGBTQQIA and neuro-diverse communities through engaged activism.